2023
DOI: 10.3389/fphar.2023.1067089
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of active compounds of a Terminalia chebula Retz. Ethanolic extract after oral administration rats using UPLC-MS/MS

Abstract: Terminalia chebula Retz. (TC) is a well-known Chinese herbal medicine and rich in chemical components with multiple pharmacological effects. In this study, an ultra-performance liquid chromatography-tandem mass spectroscopy (UPLC-MS/MS) method was developed and used to determine the blood concentrations of nine active compounds (chebulic acid, gallic acid, protocatechuic acid, corilagin, chebulagic acid, chebulinic acid, 1,2,3,4,6-O-pentagalloylglucose, ellagic acid and ethyl gallate) after oral administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Spiking of samples with reference standards also performed. Comparison with reported references was also conducted for identification of constituents 20–25 . The total ion chromatograms of LGS samples in negative and positive modes are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spiking of samples with reference standards also performed. Comparison with reported references was also conducted for identification of constituents 20–25 . The total ion chromatograms of LGS samples in negative and positive modes are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison with reported references was also conducted for identification of constituents. [20][21][22][23][24][25] The total ion chromatograms of LGS samples in negative and positive modes are shown in Figure 1. Table S1 displays the results of the identification and characterization of 162 chemicals from LGS, which included flavonoids, polyphenols, organic acids, and amino acids.…”
Section: Chemical Profiling Of Lgsmentioning
confidence: 99%
“…As depicted in Figure 4C, the CF samples were clustered into three groups with the dominant contents of chebulagic acid (95), chebulinic acid (107), and ellagic acid (110)/gallic acid (12). Chebulagic acid, chebulinic acid, and chebulic acid were screened out according to their chemotaxonomic potentials.…”
Section: Uplc-pda Fingerprinting and Multivariate Statistical Analysismentioning
confidence: 99%
“…Among the edible fruits in the Himalayan region of India, CFs with the highest antioxidant level have been used as a daily dietary supplement among people living in the mountains [11]. A recent study revealed that corilagin, chebulagic acid, and chebulinic acid in CF may be absorbed into the body for a comparatively long term to exert continuous treatment effects [12].…”
Section: Introductionmentioning
confidence: 99%
“…These phytochemicals contribute to the high antioxidant capacity and free radical scavenging activity, anti-cancer activity, antibacterial, antifungal, antiviral, and anti-inflammatory activities, as well as the wound healing and immunomodulatory activities associated with T. chebula fruit [11]. This plant, which contains various bioactive compounds [12], has thepotential to eliminate poultry-related microbes; however, there is limited research on this aspect. Therefore, the objective of this study is to investigate the effectiveness of this plant in eradicating poultryassociated microbes and to explore its potential use as a feed additive.…”
Section: Introductionmentioning
confidence: 99%